Petrografia, litoquímica e geocronologia dos enclaves hospedados nas rochas vulcânicas e plutônicas do Supergrupo Uatumã, NE de Mato Grosso - Tarelow Neto, João (2016)
At the northeast of the Mato Grosso state, southeast of the Amazonian Craton, crop out felsic and mafic magmatic microgranular enclaves, hosted by felsic volcanic and plutonic rocks. The volcanics consist of dacites, rhyolites and ignimbrites with petrographic, geochemical and geochronological features consistent with the Iriri Group. The dacite U-Pb crystallization age is of 1895±13 Ma. The granitoids are divided into syenogranite, monzogranites, U-Pb geochronology of syenogranite yielded crystallization age of 1979±10 Ma, which is consistent with the Vila Rica Intrusive Suite granitoids. Felsic and mafic enclaves show distinguishing petrographic features that suggest magma mingling processes, as diffuse and interlobated boundaries and host rock xenocrysts within the enclave. The felsic enclaves consist of granodiorites, tonalites and quartz-rich granitoids with geochemical patterns and geochronological ages that fit with the Iriri Group, suggesting comagmaticity of them. U-Pb dating of the felsic granodiorite enclave yielded three distinct ages: a crystallization Paleoproterozoic age of 1869±32 Ma; an inherited Paleoproterozoic age of 1968±30 Ma that fit with the Vila Rica Intrusive Suite age; and inherited Neoarchean ages from 2512 to 2767 Ma that fit with the crystallization age of orthogneisses of the Santana do Araguaia Complex. Therefore, the felsic enclaves can represent crust-derived magma, with restitic zircon, or a chilled margin (cognate autolith), with zircon grains dragged out from wall rocks. The mafic enclaves are classified as olivine-clinopyroxene gabbro, clinopyroxene-hornblende gabbro, biotite-clinopyroxene diorite, biotite-hornblende diorite and biotite quartz diorite. Geochemical patterns of dioritic enclaves fit with those of the Santa Inês Intrusive Suite mafic rocks, indicating comagmaticity of them. The recognition of diverse geochemical patterns of felsic and mafic enclaves suggests that the study area can represent the top of a complex shallow magma chamber that experienced several replenishment events from diverse sources. The mafic enclaves and the host volcanics of the Iriri Group are regarded as contemporaneous and attest the hypothesis that the Uatumã Supergroup felsic magmatism and the Santa Inês mafic magmatism are also contemporaneous. This assumption allows the proposition of a bimodal character for the Uatumã Magmatism at the northeast of the Mato Grosso state and that mantle magmas played an important role in the genesis of this magmatism.